2018
DOI: 10.1136/bjophthalmol-2017-311662
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravitreal conbercept injection in the treatment of retinopathy of prematurity

Abstract: IVC injection is an effective treatment for ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Our previous studies 6,7 of conbercept demonstrated similar ROP recurrence rates (6/38 and 3/20, respectively), which were consistent with a study from another team in South China (8/48). 8 In our comparative study, 7 the recurrence rate was lower with conbercept than with ranibizumab (15/28, 53.6%). Our previous study found a similar recurrence rate (45.45%) of ranibizumab.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our previous studies 6,7 of conbercept demonstrated similar ROP recurrence rates (6/38 and 3/20, respectively), which were consistent with a study from another team in South China (8/48). 8 In our comparative study, 7 the recurrence rate was lower with conbercept than with ranibizumab (15/28, 53.6%). Our previous study found a similar recurrence rate (45.45%) of ranibizumab.…”
Section: Discussionmentioning
confidence: 62%
“…A few studies have indicated that intravitreal anti-VEGF drugs induce systemic VEGF suppression for weeks to months [3][4][5] , although no significant adverse events have been reported to date. There have been occasional reports on the use of conbercept, a novel anti-VEGF agent, for ROP treatment [6][7][8] , however, the effect of conbercept on systemic VEGF concentrations in ROP has not yet been reported.…”
mentioning
confidence: 99%
“…7,[30][31][32] In addition, it was shown to have a favorable outcome effect for ROP, although well-designed clinical trials have yet to be conducted. 33,34 Given its reproducibility and consistency, the laserinduced CNV mouse or rat model has been used in the preclinical testing of biological agents for the neovascular AMD pathology. 35,36 In the present in vivo suppression study of choroidal neovascularization, VEGF-Grab showed efficacy comparable to that of aflibercept.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven to be helpful in managing different retinal neovascular diseases. [22][23][24] Literatures revealed the success of Anti-VEGF agents in treating CNV secondary to choroidal osteomas, in particular the use of Aflibercept in non-responder to bevacizumab and ranibizumab. Considering the similarity in pharmacological characteristics between Conbercept and Aflibercept, we decided to give Conbercept injection intravitreally to our case-a young female with CNV secondary to unilateral choroidal osteomas.…”
Section: Discussionmentioning
confidence: 99%